The Professional Future in Operated Carpal Tunnel Syndrome: A Cross-Sectional Study of Recognized Occupational Cases - Ben Said, Hanene; Kaabi, Khaoula; Kerkeni, Neila; Youssef, Imen; Mechergui, Najla; Brahim, Dorra; Youssfi, Imen; Mersni, Meriem; Bahri, Ghada; Hamdouni, Mongi; Ladhari, Nizar (La Medicina del Lavoro, 2023)
Background: Carpal tunnel syndrome (CTS) is frequently present among workers. This syndrome’s professional and economic impact makes it a priority in occupational health. We aimed to describe the professional future of workers suffering from occupational CTS after surgery and the factors that could influence their retention at the job. Methods: A retrospective descriptive study of workers operated on occupational CTS was conducted from 2014 to 2019. The data was collected using pre-established and phone questionnaires to determine their professional future after surgery. Results: We included 99 workers with operated CTS. They had a mean age of 45±6.5 years, were predominantly female (97%), and had two dependent children in 72.7% of cases. They worked as a seamstress in 44.4% of patients with a mean professional seniority of 18±7.2 years. The professional future was a return to work with a job transfer at 44.4% and job maintenance with ergonomic adjustments at 39.4%. A job loss was noticed in 12.2% of cases. Early retirement was noticed in 8.2%, dismissal in 3%, and resignation in 1% of cases. The factors influencing the professional future were age 50 to 59 years (p=0.01) and dependent children (p=0.02). Conclusions: In our survey, most operated-CTS workers benefited from a job transfer and kept their job with ergonomic adjustments to their work conditions. Therefore, interventions aiming to improve the professional future of workers operated on CTS by ensuring sufficient staff and adjusting workplaces are needed.